1994
DOI: 10.1084/jem.179.6.1945
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid residues that flank core peptide epitopes and the extracellular domains of CD4 modulate differential signaling through the T cell receptor.

Abstract: StlmmaryHen egg lysozyme 52-61-specific CD4 + T cells responded by interleukin 2 (IL-2) secretion to any peptide containing this epitope regardless of length of NH2-and COOH-terminal composition. However, CD4-variants could only respond to peptides containing the two COOHterminal tryptophans at positions 62 and 63. Substitutions at these positions defined patterns of reactivity that were specific for individual T cells inferring a T cell receptor (TCR)-based phenomenon. Thus, the fine specificity of major hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 86 publications
1
46
0
Order By: Relevance
“…LAG-3 expressing T cell hybridomas were transduced as described (30) using the CD4 Ϫ variant T hybrid (3A9.N49; H-2A k -restricted, hen egg lysozyme (48 -63-specific) (31). LAG-3 expression was uniformly high in all transductants.…”
Section: Lag-3-transfected N49 T Cell Hybridomasmentioning
confidence: 99%
“…LAG-3 expressing T cell hybridomas were transduced as described (30) using the CD4 Ϫ variant T hybrid (3A9.N49; H-2A k -restricted, hen egg lysozyme (48 -63-specific) (31). LAG-3 expression was uniformly high in all transductants.…”
Section: Lag-3-transfected N49 T Cell Hybridomasmentioning
confidence: 99%
“…Assays were performed essentially as previously described by Vignali and Strominger with slight modifications (28). In all assays B lymphoma cells (A-20) were used as APCs and labeled with a given peptide overnight before each assay.…”
Section: Ag Presentation Assay With T Cell Hybridomasmentioning
confidence: 99%
“…It has been shown that residues flanking the core peptide might be involved in the interaction between the TCR and the MHC class II-peptide complex [36,52]. However, we could show that the HLA-DR Ã 1101 tetramers loaded with the anchor-tailored analogues enriched a population of specific T cells able to recognize also the WT peptide and displaying a rather clonally heterogeneous T-cell repertoire.…”
Section: Discussionmentioning
confidence: 59%